Spectrophotometric Determination of Famciclovir and Racecodotril Using 2, 6-Dichloroquinone–Chlorimide - M. Vamsi Krishna; P. V. Madhavi Latha; D. Gowri Sankar (E-Journal of Chemistry)
A simple, sensitive spectrophotometric method for the determination of Famciclovir and Racecodotril is developed. It is based on the formation of a colored oxidative coupling product between 2,6-dichloroquinone-chlorimide and the drug is described. The method has been extended to pharmaceutical preparations. The absorption maxima and Beer’s law limits for Famciclovir are 500 nm, 20-100 µg/mL and for Racecodotril are 460 nm, 12.5-62.5 µg/mL.